Enhanced CO2 sorption capacity of amine-tethered fly ash residues derived from co-firing of coal and biomass blends. (15th May 2019) - Zhao, Chuanwen; Guo, Yafei; Yan, Junjie; Sun, Jian; Li, Weiling; Lu, Ping
Highlights: Co-firing fly ash was impregnated with TEPA to fabricate CO2 sorbent. TFA-25 exhibited good CO2 sorption and sorbent regeneration performance. Operating parameters for CO2 sorption and sorbent regeneration were optimized. The amine-tethered sorbent retained stable CO2 uptake in repeated cycles. Recycling co-firing fly ash presented environmental and economic implications. Abstract: Co-firing of coal and biomass blends provides a promising route for clean energy utilization with high efficiency and mitigated pollutants emission. However, the technology meets an important challenge in effective utilization of the co-firing fly ashes. Efforts have been made to valorize the co-firing fly ash residues as potential CO2 sorbents. To achieve enhanced CO2 sorption performance, the samples were modified with tetraethylenepentamine (TEPA). Effects of amine loading, CO2 sorption temperature, initial CO2 concentration and gas flow rate on CO2 sorption behaviors of the amine-tethered sorbents were investigated. The desired sorbent with 25% TEPA loading presented the highest CO2 sorption capacity of 1.19 mmol CO2 /g when tested under 60 °C and 15%CO2 with a total gas flow rate of 1200 ml min −1 . The effects of regeneration temperature and ramping rate on sorbent regeneration performance were demonstrated. The maximum sorbent regeneration efficiency of 97.2% was achieved under the regeneration condition of 110 °C and 5 °C min −1 . CO2 sorption capacity of the amine-tethered sorbent kept stable within 5 repeated cycles. These findings indicate that the amine-tethered sorbent could be a good candidate for on-site CO2 capture from flue gas in co-firing power plants.